Antifungal drug resistance: evolution, mechanisms and impact. (October 2018) - Revie, Nicole M; Iyer, Kali R; Robbins, Nicole; Cowen, Leah E
Graphical abstract: Highlights: Our limited arsenal of antifungals is threatened by drug-resistant fungal pathogens. Inherent resistance is when all strains of a species show antifungal resistance. Target alteration and drug efflux are canonical adaptive resistance mechanisms. Stress responses are important mediators of resistance to diverse antifungals. Agricultural use of antifungals may drive the development of resistance. Abstract : Microorganisms have a remarkable capacity to evolve resistance to antimicrobial agents, threatening the efficacy of the limited arsenal of antimicrobials and becoming a dire public health crisis. This is of particular concern for fungal pathogens, which cause devastating invasive infections with treatment options limited to only three major classes of antifungal drugs. The paucity of antifungals with clinical utility is in part due to close evolutionary relationships between these eukaryotic pathogens and their human hosts, which limits the unique targets to be exploited therapeutically. This review highlights the mechanisms by which fungal pathogens of humans evolve resistance to antifungal drugs, which provide crucial insights to enable development of novel therapeutic strategies to thwart drug resistance and combat fungal infectious disease.